The Relationship between Environment and Physical Fitness on Physical Education Learning Outcomes and Al-Quran Tahfidz Ability of Middle School Students - Andica, Ultrio Lipu; Welis, Wilda; Syahrastani, Syahrastani; Chaeroni, Ahmad; Ockta, Yovhandra (STKIP Singkawang, 2024)
The problem in this research is the low ability of learning outcomes (physical education learning outcomes and the ability to recite the Koran) as well as the low fitness of students. The purpose of this research is to determine the relationship between learning environmental factors and physical fitness on physical education learning outcomes and the ability to tahfidz Al-Quran students at Junior High School ICBS Payakumbuh, Harau Putra. The type of research is simple regression correlation with a population of 155 students at Junior High School ICBS Payakumbuh, Harau Putra. The sample in this research was 30 people, the technique used in sampling was the Stratified Proportional Random Sampling technique by taking 20% samples at each class level. The research instrument used used were questionnaire statement sheets, Indonesian student fitness tests (TKSI), and physical education learning outcomes and Al-Quran tahfidz. Data analysis techniques were carried out using normality tests and homogeneity tests with the help of SPSS 22 software. Hypothesis test results used product moment correlation tests with manual calculations at a 95% confidence level α = 0.05. The results of research data analysis show that: (1) There is a correlation between learning environmental factors and students' physical education learning outcomes of 79.8% (2) There is a correlation between learning environmental factors with students' Al-Quran tahfidz ability of 33.1% (3) There is The relationship between physical fitness and students' physical education learning outcomes is 87.8% (4) There is a relationship between physical fitness factors and the ability to recite the Al-Quran by 23% (5) There is a relationship between learning environment factors and physical fitness on physical education learning outcomes amounting to 91.7% (6) There is a relationship between learning environmental factors and physical fitness on the ability to tahfidz Al-Quran amounting to 35.5%.